Room-temperature ferromagnetism via unpaired dopant electrons and p-p coupling in carbon-doped In2O3 : experiment and theory - Kurmaev, E. Z. (2013)
Observations of magnetism in semiconductors doped with nonmagnetic atoms (C, N, etc.) show promise for spintronics applications, but pose an interesting challenge for conventional theories of magnetism. In this work, the magnetic semiconductor carbon-doped In2O3 is studied using theoretical and experimental techniques. Density-functional theory calculations predict that ferromagnetism can exist near room temperatures when substitutional carbon atoms have a formally unpaired 2p electron that does not participate in bonding. The unpaired 2p electrons lead to an impurity band near the Fermi level and consequent enhanced density of states which accommodates a strong p-p coupling between local magnetic moments. The unpaired electrons and ferromagnetic coupling are found to arise from a combination of interstitial and substitutional carbon atoms in close proximity. Finally, experimental measurements on samples with varying magnetic properties verify the importance of both strong C 2p character at the Fermi level and strong C 2sp-In 4d hybridization for yielding room-temperature ferromagnetism. These results shed light on the interesting field of nonmagnetic dopants inducing ferromagnetism in semiconductors.